OP112 Project Management for EUnetHTA Non-Pharmaceutical Technologies. (2019) - De Villiers, Cecilia; Ettinger, Sabine; Erdos, Judit
Abstract : Introduction: The European Network for Health Technology Assessment (EUnetHTA) facilitates and produces Health Technology Assessments (HTA) across Europe. Project Management (PM) provides the coordination and strategic overview of assessment production and enables the flow of scientific knowledge and assessment publications through collaboration and standardized processes, procedures and documentation. Methods: EUnetHTA established a central PM function at the Ludwig Boltzmann Institute for HTA (LBI-HTA) for central coordination and assessment production of non-pharmaceutical technologies. LBI-HTA subsequently pursued capability and capacity through a decentralized hub-and-spoke-PM model with six activity centers (AC) providing decentralized coordination and PM of assessments. LBI-HTA provided central oversight and supervision with training days, e-meetings and ad hoc e-mail and telephone support as required. This was complemented by standardized operating procedures (SOPs) in the online Companion Guide (CG). A qualitative data collection via electronic questionnaires collected feedback from AC-PM, LBI-HTA-PM and assessment authors. Specific questions with free-text responses assessed current experiences, challenges, recommendations, communication and task distributions of the centralized and decentralized PM processes from these different perspectives. Results: The feedback concluded that PM is a separate, well-defined and important role for assessment coordination and production. The AC-PM received adequate training from the central PM and authors experienced no difference between projects managed centrally or decentrally. The CG and SOPs are important for guiding standard practice and allowing AC-PM to operate independently. Challenges were around extended timelines due to complex topics, external stakeholder involvement, insufficient team communication and not yet published SOPs resulting in additional central support. Conclusions: Decentralized coordination of assessments, knowledge management and governance achieve scale, capacity and capability through a designated pool of agencies with established roles and growing experience in sustainable collaboration of HTA production. Valuable insight into the PM model's operational efficiency, avoidance of duplication and resource savings potentially provides a sustainable post 2020 European network policy and efficiency model for high quality HTA assessment production.